Studies on Optimisation of Bridle Lengths for Demersal Trawls - K.V., Mohan Rajan; M.R., Boopendranath; P., George Mathai; N., Subramonia Pillai (Fishery Technology, 2025)
Experiments were carried out to standardise the length of bridles in a 32 m large mesh dtmsrsal trawl and a 25 m high opening dzmersal trawl. Based on the compara- tive catch rates obtained, double bridles of 30 m length was adjudged a better choice for a 25 m high opening trawl whereas, 20 m bridles were found to improve the performance of 32 m large mesh trawl.